PENGARUH KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. WIRA GARDA PERKASA - Murvanto, Oka Agus; Maranata, Bonaventura Hendrawan (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to determine (1) The Effect of Discipline on Employee Performance of PT Wira Garda Perkasa. (2) The Effect of Work Motivation on Employee Performance of PT. Wira Garda Perkasa. (3) The Effect of Discipline and Performance Motivation on Employee Performance of PT. Wira garda Perkasa. This research is Quantitative research. The population of this study consisted of personnel of PT Wira Garda Perkasa totaling 109 respondents. One method of data collection is the use of a questionnaire. The data processing tool used is SPSS 26.0 for Windows. According to the research findings, (1) with a t value of 9.318> t table 1.65922 and a significance level of 0.000, discipline (X1) significantly and positively affects employee performance (Y). (2) with a calculated t value of 2.368> t table of 1.65922 and a significance level of 0.020, Work Motivation (X2) has a positive and significant effect on Employee Performance (Y). Employee discipline and motivation increase with clear and challenging targets, supported by a corporate culture that values punctuality, achievement, and cooperation.